Energy Analysis Produced In Mixture of Liquid (Pertalite) and Gas (LPG) in Conventional Machine 4 Cylinder - Adi Pratama Putra; Ikhwanul Qiram (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
Increased mobility of transportation plays a major role in the economic growth of a region. Despite the rapid growth of the automotive industry, there are still quite a lot of people who use old-type vehicles to support their mobility. Conventional 4-cylinder engine is one type of engine that is widely used in public transportation modes. The purpose of this study was to obtain an analysis of the energy produced in a mixture of liquid fuel (pertalite) and gas (LPG) in a conventional engine 4-cylinder. The research method used was an experiment, carried out on a conventional engine 4-cylinder. A dynamometer is used to determine the power and torque produced. As for testing the rate of fuel consumption using a measuring burette, then the fuel consumption is calculated. The research data are arranged in tables and graphs to obtain the analysis of the energy produced at each rotation speed variation (Rpm). The results showed there were differences in power, torque and fuel consumption produced by a mixture of the two types of fuel used. For maximum power generated at a standard injector variation that uses Pertamax plus fuel of 11.61 kW and a maximum torque of 12.98 Nm. While the lowest power is produced by Pertamax using a racing injector of 2.26 kW and the lowest torque of 8.67 Nm. The lowest fuel consumption is obtained from the use of a standard fuel injector Pertamax plus of 0.12 kg / kW while the highest fuel consumption produced by Pertamax Plus uses a standard injector of 1.28 kg / kW.